Content rules : how to create killer blogs, podcasts, videos, Ebooks, webinars (and more) that engage customers and ignite your business - Handley, Ann, 1963- (New rules of social media series., 2012)
"How do you create the stories, videos, and blog posts that cultivate fans, arouse passion for your products and services, and ignite your brand? Content Rules equips you for online success as a go-to guide to the art and science of developing content that people care about. Case studies show how companies have successfully spread their idea through blogs, YouTube, Facebook, Twitter, Google+, and other platforms - and use them to establish credibility and build a loyal customer base"--